Aktivitas Sitotoksik Ekstrak Etanol Daun Aglaia elliptica Blume terhadap Galur Sel Kanker Serviks (HeLa) - WAHONO SUMARYONO; AGUN ERU WIBOWO (Fakultas Farmasi Universitas Pancasila, 2010)
Cytotoxicity tests on ethanol extract of Aglaia elliptica Blume leaves and its fractions on cervical cancer cell line (HeLa) were carried out. Dried powder of Aglaia elliptica leaves was extracted using ethanol andthen fractionated by n-hexane, ethyl acetate, and buthanol solvents. The cytotoxicity tests using MTT method (prolipheration inhibiton test) on HeLa cell lines were conducted for ethanol extract, n-hexana, ethyl acetate, and buthanol lractions.The results showed that the ethanol extract of Aglaia elliptica and its fractions have inhibition effect against HeLa cell line with IC50 of 282.44 ppm, 177.64 ppm, 16.03 ppm, 211.77 ppm, 181.33 ppm for ethanol extract, n-hexane, ethyl acetate, buthanol, and Water fractions respectively.